Protestantes taiwaneses em São Paulo: a fundação da Primeira Igreja Presbiteriana de Formosa de São Paulo - um estudo de caso - Tolentino, Marcello Cliffton (2017)
This paper is aimed at the study of migration among the Taiwanese people coming to Brazil, to the city of Sao Paulo. It is a case study of a Christian community organized in Sao Paulo and the foundation of a church here in 1962, the First Presbyterian Church of Formosa of Brazil. The research was based in the field of ethnical identity according to the proposals of Roberto Cardoso de Oliveira. In order to understand that migration movement, its development, the difficulties and challenges faced and how the church was organized we are going to study China and Taiwan history and rely mainly on the memories of the people. Specific bibliography about the Taiwanese migrating to Brazil is almost inexistent. We want to tell a story and write it so it will not be lost or forgotten.